Penyelesaian Pelanggaran Kode Etik Profesi Bagi Anggota Kepolisian Yang Melakukan Tindak Pidana Penganiayaan (Studi Kasus Pada Polda Maluku) - Dinnera Ester Agatha Suripatty; Elsa Rina Maya Toule; Yanti Amelia Lewerissa (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: The National Police is an agency that protects public safety, but now many people are caught committing acts that disturb security and even abuse the community. The existence of these violations adds to the long black list of increasing violations of discipline and the code of ethics committed by members of the National Police.Purposes of the Research: know the procedures for the judicial process and settlement of violations of the Professional Code of Ethics against members of the Ambon City Police who commit criminal acts of persecution. As well as to find out the form of sanctions against members of the Ambon City Police who committed criminal acts of persecutionMethods of the Research: The type of research used in this study is empirical juridical. The research location is the Maluku Regional Police. The population is the entire research unit that will be examined and then analyzed.Results of the Research: There is a Court Decision No.29/Pid.B/2021/PN.Amb which handed down the TK Iptu with criminal decisions and other cases of abuse committed by the TK Iptu. Disciplinary Sanctions that do not cause a deterrent effect and the implementation of the KKEP trial have followed the procedures as in Police Regulation Number 7 of 2022 concerning the Professional Code of Ethics and the Code of Ethics Commission, so the KKEP Decision (Professional Code of Ethics Commission) in the case of PTDH examined Iptu Kindergarten is in accordance with procedures within the National Police as well as in a code of ethics hearing by the Professional Code of Ethics Commission (KKEP) decided that the Iptu TK was dismissed with a dishonorable discharge decision (PTDH). The violators are now making an appeal by submitting it to the appeals commission and are currently in the administrative process.